PENGEMBANGAN BAHAN AJAR KEWIRAUSAHAAN BERBASIS DIGITAL MARKETING DENGAN MEDIA MARKETPLACE UNTUK MENINGKATKAN MINAT BERWIRAUSAHA MAHASISWA - Afief Maula Novendra; Sri Marten Yogaswara; Aini Kusniawati (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Development of Digital Marketing-Based Entrepreneurship Teaching Materials with Media Marketplace to Increase Student Entrepreneurial Interest. This development research aims to: (1) Develop digital marketing-based entrepreneurship teaching materials with marketplace media. (2) The steps for implementing digital marketing-based entrepreneurship teaching materials with marketplace media. This development research refers to the development design steps developed by Dick and Carey which were adapted by Gall et al. The development design is grouped into three development procedures, which include: (a) the planning stage (planning), (b) the design stage (design ), and (c) the development stage (development). This research produces (1) Digital marketing-based entrepreneurship teaching materials with the https://kantunwantun.com/ marketplace media and is equipped with instructions that can be accessed by students, (2) Implementation steps digital marketing-based entrepreneurship teaching materials with marketplace media https://kantunwantun.com. Suggestions in this study for the development of teaching materials are carried out within the campus internal environment, in the future continue research on developing teaching materials digital marketing-based entrepreneurship teaching materials with marketplace media involving lecturers , teachers and practitioners by conducting focus group discussions (FGD) and Marketplace https://kantunwantun.com/ in the future it will be more developed with attention to MSMEs and students to be able to collaborate to create new entrepreneurs.